The Effect of Media Literacy and Cognitive Ability on Recognition Laptop-Based Media for Children - Mainofriwita; Hadiyanto (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Education has long been the target of utopian interventions, and with technological interventions, offering to change drastically or even eliminates classroom-based learning, traditional education research needs to focus on introducing technology tools at an early age through media literacy. The purpose of this study was to determine the effect of media literacy and cognitive abilities on the introduction of laptop-based media. This study used a quasi-experimental design involving 46 children. Data collection techniques through tests and data collection tools using statement sheets, which were processed using t-test. The results showed that the experimental class using the original laptop media had a high average value of 86.66 compared to the control class using the imitation laptop media which had a value of 81.66. There is a significant effect of media literacy and cognitive ability on the introduction of laptop-based media in children. On the introduction of laptop-based media in children, media literacy and cognitive capacities can have a big impact. The comparison of the average value of the control and experimental classes demonstrates this. When children are introduced to media via a genuine laptop, they become more excited and engaged in the experimental lesson. Keywords: media literacy, cognitive ability, laptop-based learning media References: Adams, D., & Hamm, M. (2001). Literacy in a multimedia age. MA: Christopher- Gordon Publishers. Ames, M. G. (2016). Learning consumption: Media, literacy, and the legacy of One Laptop per Child. The Information Society, 32(2), 85–97. https://doi.org/10.1080/01972243.2016.1130497 Arsyad. (2013). Media Pembelajaran [Learning Media]. Raja Grafindo Persada. Bedford, D. (2021). Evaluating confidence in information literacy: A red/amber/green approach. Journal of Information Literacy, 15(1), 96–104. https://doi.org/10.11645/15.1.2833 Buckingham, D., Banaji, S., Burn, A., Carr, D., Cranmer, S., & Willett, R. (2015). The Media Literacy of Children and Young People (p. 76). Youth and Media Institute of Education. www.ofcom.org.uk Campbell, D. T., & Stanley, J. C. (2015). Experimental and Quasi-Experimental Designs for Research. Ravenio Books. https://books.google.co.id/books?id=KCTrCgAAQBAJ Colom, R., Escorial, S., Shih, P. C., & Privado, J. (2007). Fluid intelligence, memory span, and temperament difficulties predict academic performance of young adolescents. Personality and Individual Differences, 42(8), 1503–1514. https://doi.org/10.1016/j.paid.2006.10.023 Dodonova, Y. A., & Dodonov, Y. S. (2012). Processing speed and intelligence as predictors of school achievement: Mediation or unique contribution? Intelligence, 40(2), 163–171. https://doi.org/10.1016/j.intell.2012.01.003 Ebbeck, M., Yim, H. Y. B., Chan, Y., & Goh, M. (2016). Singaporean Parents’ Views of Their Young Children’s Access and Use of Technological Devices. Early Childhood Education Journal, 44(2), 127–134. https://doi.org/10.1007/s10643-015-0695-4 Faigenbaum, G., Sigman, M., & Casiraghi, L. P. (2018). Young Children Use Discovery and Creation Significantly More Than Adults for Deciding Ownership. Child Development Research, 2018(4). https://doi.org/10.1155/2018/1517904 Ferguson, B. A., Downey, J. L., Shriver, A. E., Goff, K. L., Ferguson, A. M., & De Mello, M. C. (2018). Improving Early Childhood Development among Vulnerable Populations: A Pilot Initiative at a Women, Infants, and Children Clinic. Child Development Research, 2018. https://doi.org/10.1155/2018/3943157 Hirsh-Pasek, K., Zosh, J. M., Golinkoff, R. M., Gray, J. H., Robb, M. B., & Kaufman, J. (2015). Putting Education in “Educational” Apps: Lessons from the Science of Learning. Psychological Science in the Public Interest, 16(1), 3–34. https://doi.org/10.1177/1529100615569721 Hobbs, R. (2011). The state of media literacy: A response to potter. Journal of Broadcasting and Electronic Media, 55(3), 419–430. https://doi.org/10.1080/08838151.2011.597594 Hwang, G.-J., Lai, C.-L., & Wang, S.-Y. (2015). Seamless flipped learning: A mobile technology-enhanced flipped classroom with effective learning strategies. Journal of Computers in Education, 2(4), 449–473. https://doi.org/10.1007/s40692-015-0043-0 Juditha, C. (2013). Literasi Media pada Anak di Daerah Perbatasan Indonesia dan Timor Leste [Media Literacy for Children in the Border Areas of Indonesia and Timor Leste]. JURNAL IPTEKKOM: Jurnal Ilmu Pengetahuan & Teknologi Informasi, 15(1), 47. https://doi.org/10.33164/iptekkom.15.1.2013.47-62 Kaushal S and Singh CK. (2021). Home Stimulation and Cognitive Abilities of Disadvantaged Children. Journal of Scientific Research, 65(1). https://doi.org/DOI: 10.37398/JSR.2021.650413 Kellner, D., & Share, J. (2007). Critical Media Literacy, Democracy, and the Reconstruction of Education. Peter Lang Publishing. www.centerxgseis.ucla.edu Leena Rantala. (2011). Finnish Media Literacy Education Policies and Best Practices in Early Childhood Education and Care Since 2004. The National Association for Media Literacy Education’s Journal of Media Literacy Education, 3, 123–133. Liu, W., Tan, L., Huang, D., Chen, N., & Liu, F. (2021). When Preschoolers Use Tablets: The Effect of Educational Serious Games on Children’s Attention Development. International Journal of Human–Computer Interaction, 37(3), 234–248. https://doi.org/10.1080/10447318.2020.1818999 Livingstone, S., Marsh, J., Plowman, L., & Fletcher-Watson, B. (2015). Young Children (0-8) and Digital Technology(p. 55). Joint Research Centre. http://publications.jrc.ec.europa.eu/repository/handle/JRC93239 Macias, C., & Choi, K. (2021). Preschoolers’ beliefs about media technologies: The role of family income. Human Behavior and Emerging Technologies, 3(4), 572–584. https://doi.org/10.1002/hbe2.278 Papadakis, S., Kalogianakis, M., Sifaki, E., & Monnier, A. (2021). Editorial: The Impact of Smart Screen Technologies and Accompanied Apps on Young Children Learning and Developmental Outcomes. Frontiers in Education, 6, 790534. https://doi.org/10.3389/feduc.2021.790534 Papadakis, S., & Kalogiannakis, M. (2017). Mobile educational applications for children: What educators and parents need to know. Int. J. Mobile Learning and Organisation, 11(3), 22. Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2016a). Developing fundamental programming concepts and computational thinking with ScratchJr in preschool education: A case study. International Journal of Mobile Learning and Organisation, 10(3), 187. https://doi.org/10.1504/IJMLO.2016.077867 Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2016b). Comparing Tablets and PCs in teaching Mathematics: An attempt to improve Mathematics Competence in Early Childhood Education. Preschool and Primary Education, 4(2), 241. https://doi.org/10.12681/ppej.8779 Potter, W. J. (2010). The state of media literacy. Journal of Broadcasting and Electronic Media, 54(4), 675–696. https://doi.org/10.1080/08838151.2011.521462 Ren, X., Tong, Y., Peng, P., & Wang, T. (2020). Critical thinking predicts academic performance beyond general cognitive ability: Evidence from adults and children. Intelligence, 82, 101487. https://doi.org/10.1016/j.intell.2020.101487 Rusydiyah, E. F., Ummah, F. S., & Mudlofir, A. (2020). The Implementation of Laptop Mobile in the Teaching-Learning Process in Islamic Boarding School. TARBIYA: Journal of Education in Muslim Society, 7(1), 67–77. https://doi.org/10.15408/tjems.v7i1.13650 Salomon, G. (1990). Cognitive Effects with and Of Computer Technology. Communication Research, 17(1), 26–44. https://doi.org/10.1177/009365090017001002 Schaeffer, J. (2021). The influence of cognitive abilities on article choice and scrambling performance in Dutch-speaking children with autism. Language Acquisition, 28(2), 166–194. https://doi.org/10.1080/10489223.2020.1724293 Seftiani, I. (2019). Alat Evaluasi Pembelajaran Interaktif Kahoot pada Mata Pelajaran Bahasa Indonesia di Era Revolusi Industri [Kahoot Interactive Learning Evaluation Tool for Indonesian Language Subjects in the Industrial Revolution Era] 4. 0. Prosiding Seminar Nasional Bulan Bahasa (Semiba) 2019, 284–291. Syarah, E. S., Mayuni, I., & Dhieni, N. (2020). Understanding Teacher’s Perspectives in Media Literacy Education as an Empowerment Instrument of Blended Learning in Early Childhood Classroom. JPUD - Jurnal Pendidikan Usia Dini, 14(2), 201–214. https://doi.org/10.21009/JPUD.142.01 Trimmel, M., & Bachmann, J. (2004). Cognitive, social, motivational and health aspects of students in laptop classrooms. Journal of Computer Assisted Learning, 20(2), 151–158. https://doi.org/10.1111/j.1365-2729.2004.00076.x Zou’bi, R. A.-. (2021). The impact of media and information literacy on acquiring the critical thinking skill by the educational faculty’s students. Thinking Skills and Creativity, 39, 100782. https://doi.org/10.1016/j.tsc.2020.100782